Respuesta :
easy
that just means p(x)-q(x)=
x²-1-(5(x-1))=
x²-1-5(x-1)=
x²-1-5x+5=
x²-5x+4
(which factors to (x-4)(x-1) btw)
that just means p(x)-q(x)=
x²-1-(5(x-1))=
x²-1-5(x-1)=
x²-1-5x+5=
x²-5x+4
(which factors to (x-4)(x-1) btw)
Answer: The required equivalent expression is [tex]x^2-5x+4.[/tex]
Step-by-step explanation: We are given the following two functions :
[tex]p(x)=x^2\\\\q(x)=5(x-1).[/tex]
We are to find the expression equivalent to (p - q)(x).
We know that
for any two functions f(x) and g(x),
[tex](f-g)(x)=f(x)-g(x).[/tex]
Therefore, we get
[tex](p-q)(x)\\\\=p(x)-q(x)\\\\=(x^2-1)-(5x-5)\\\\=x^2-1-5x+5\\\\=x^2-5x+4.[/tex]
Thus, the required equivalent expression is [tex]x^2-5x+4.[/tex]